PORTRAYAL OF ISLAMIC FUNDAMENTALISM IN PAKISTANI NEWSPAPERS: A CRITICAL DISCOURSE STUDY - Muhammad Yaseen; Dr. Umara Shaheen (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study aims to critically analyze the discursive representation of Islamic fundamentalism in Pakistani newspapers. Thirty newspaper articles were selected from the two prominent newspapers of Pakistan, Daily Dawn and The International News, from January to December 2023. The research used Fairclough’s three-dimensional model to examine how lexical and grammatical choices used in newspaper articles shape public perception and impact societal attitudes, intergroup relations, and national security. The study found that Pakistani newspapers often frame Islamic fundamentalism not very negatively but somehow associate it with threats like terrorism. The research highlights the key themes contributing to the negative portrayal of Islamic fundamentalism, such as the association of Islam with violence, radical Islam, fear of Islam, terrorism, and the portrayal of ISIS and the Taliban. It demonstrates how language, beliefs, and power relations intersect to shape the narrative of Islamic extremism.